Integrated evaluation of the requirements and excretions of Cu, Fe, Zn, and Mn for broilers via a uniform design method - Qiu, Kai; Chen, Zhimin; Chang, Wenhuan; Zheng, Aijuan; Cai, Huiyi; Liu, Guohua (Frontiers in Veterinary Science, 2023)
This study aimed to determine the ideal balance profile of Cu, Fe, Zn and Mn for broilers with 1 to 21 day-age via uniform experimental design. In Exp. 1, nine hundred 1-day Arbor Acres male broilers were randomly allotted to 15 dietary treatments with 6 replicates of 10 birds. Fourteen experimental diets were formulated with the supplementation of 8~16, 123~160, 40~80 and 60~120 mg/kg Cu, Fe, Zn and Mn respectively in the basal diet according to uniform design method. The growth performance and excretion of Cu, Fe, Zn and Mn in the manure of broilers was determined to build the ideal balance profile of these elements. Exp. 2 was conducted based on the ideal balance profile built in Exp.1 to testify its practicability using 720 broilers with two treatments. Dietary concentrations of Cu, Fe, Zn, and Mn in control group were 15.19, 203.08, 76.78, and 86.13 mg/kg, respectively. The results of Exp. 1 showed that when the concentrations of Cu, Fe, Zn and Mn in diets were 16.96, 166.66, 46.01 and 60.26 mg/kg, respectively, the average daily gain reach the optimum value. When dietary concentrations of Cu, Fe, Zn and Mn were 8.54, 130.66, 38.19, 64.07 mg/kg, respectively, the total excretion of Cu, Fe, Zn and Mn got the minimum value. There are corresponding ideal balance profiles for minimum excretion of certain element. In Exp.2, dietary levels of Fe, Zn, and Mn were decreased 17.93%, 40.08%, and 30.04% respectively, which had no significant effect on average daily gain, average daily feed intake and feed: gain for 1~21 days broiler, but markedly decreased the excretion of Cu, Mn and total excretion. It was concluded that there is a dilemma between growth performance and mineral excretion. Although dietary levels of Cu, Fe, Zn and Mn supporting optimal growth is higher than those for minimizing mineral excretion, supplementing too much trace elements in diets of broilers are unnecessary.